A flexible mid-term frequency domain scheduler for resource allocation in Hetnets based on the SINR requested by users (2014)
This article solves the resource allocation problem for the downlink of a multi-cell, multiservice Wireless Mobile Communications System (WMCS) with heterogeneous architecture deployed into an urban environment using Orthogonal Frequency Division Multiple Access (OFDMA) in its physical level. The optimization model aims to equitably satisfy services to users by making an efficient use of the available resources using the Signal to Interference-plus-Noise Ratio (SINR). It is a Mixed Integer Nonlinear Programming (MINLP) model whose solution is complex to obtain directly. The proposed solution algorithm decouples the solution space of the problem and uses an iterative and distributed approach to implement a frequency-domain scheduler in the medium term that uses a global vision of the system to allocate resources trying to obtain the SINR required for all users (the proposed goal). Since it is not always possible to achieve the proposed goal, we take advantage of the elasticity of some of the services offered and incorporating the slack variable ΔPref to solve it. The approach allows selecting the frequency allocation strategy, the exploration focus of the search space and the system administrator's vision.